Triangles and Hopes for Accuracy - Between Armchair Geography and Field Geography: Discourse and Cabinet of Juan Polo y Catalina - Fuentes Crispín, Nara (Pontificia Universidad Javeriana, 2014)
This article inquires about the role of empirical knowledge in the genesis of Geography in Spain in the late eighteenth century. To do so, it focuses on the analysis of a document written by the cartographer Juan Polo y Catalina titled “Discourse on the need to ascertain the productive surface of the states, work done with this purpose by all the powers of Europe, and means used to know it”. This analysis raises the issue of image, as well as topics related to map-building such as the combination of theory and practice, the progressive impulse, the quest for productivity in the Spanish provinces and, significantly, the limitations and findings of this technical exercise in achieving accuracy as a key element of the pursuits of Geography.